(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
In life, sorting is one of the basic human intuitive skills that is taught at a young age. In computer science, sorting has broad applications from database management systems to data science and from data structures to machine learning and deep learning. sorting is the primary process which transforms the raw data into useful information. Over the years many algorithms of sorting have been discovered and put forward; all of the introduced approaches have brought new perspectives to solve the same problem, Mean Sort is an algorithm that operates on the unsorted array, computes the arithmetic mean and compares the mean with each element. A recursive approach is used to reach the solution in an efficient time. Mean Sort performs better than the well-established algorithms which are Quick Sort, Merge Sort and Heap Sort. This fact also acts as evidence that Mean Sort is better than the Bubble Sort, Insertion Sort and Selection Sort. This work consists of introduction, operational understanding and performance analysis of Mean Sort. This introduced approach to sorting ensures the time efficiency of the Quick Sort is maintained along with the preservation of stability of the Merge Sort.